Sosialisasi Digital Marketing dan Manajemen Keuangan Pada Pelaku UMKM di Kelurahan Sukorejo Kota Blitar - Tiara Febry Adviola; Nico Akbar Priyambudi; Annisa Aprilia Husnul Khotimah; Danurwenda Permana Erlushandy; Gideon Setyo Budiwitjaksono (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
This socialization is a form of community service, especially MSME actors and residents of the Sukorejo Village, Blitar City. With the socialization of MSME development, it is hoped that it can increase the knowledge, insight, and understanding of business people in the Sukorejo Village so that they can adapt to the times and in running a business by utilizing the existing potential. Business actors and residents of the Sukorejo Village are given an understanding of the importance of online marketing or what is commonly called digital marketing, the importance of making a logo as an identity and marketing strategy as well as managing financial business. The implementation of this service program was carried out using the lecture method by UPN Veteran Jatim students and also one of the lecturers followed by a question and answer session. The results of this socialization are 1.) Very good enthusiasm seen from the activeness of the audience in listening and asking questions 2.) This MSME development outreach program can be of good use and can be applied by the audience in running their business. Socialization, Digital marketing, MSME